Analysis of microgrid inverter droop controller with virtual output impedance under non‐linear load condition. Issue 6 (1st June 2014) - Wang, Wen; Zeng, Xiangjun; Tang, Xin; Tang, Ci
Abstract : With the existence of virtual impedance, the load harmonic currents would decrease the detection accuracy of fundamental power calculated in DQ method, thus influence the performance of droop control system in microgrid inverters. Quantitative analysis of the fundamental power detection error is conducted and general expressions of inverter output power in the presence of virtual impedance are established. The concept of virtual harmonic power is proposed to approximately describe the error. Furthermore, the small signal stability analysis method is applied to present a detailed performance analysis of the control system as virtual harmonic power is taken into consideration. The analysis indicates that under the non‐linear load condition, the value of droop coefficients and the type of designed virtual output impedance will influence the stability of the control system, which means that droop coefficients and virtual output impedance should be carefully selected to gain sufficient stability margin. Simulation and experiment are both carried out and comparison of linear and non‐linear load condition is presented in detail which verifies the theoretical analysis.